b+61/3=-4

Simple and best practice solution for b+61/3=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b+61/3=-4 equation:



b+61/3=-4
We move all terms to the left:
b+61/3-(-4)=0
We add all the numbers together, and all the variables
b+4+61/3=0
We multiply all the terms by the denominator
b*3+61+4*3=0
We add all the numbers together, and all the variables
b*3+73=0
Wy multiply elements
3b+73=0
We move all terms containing b to the left, all other terms to the right
3b=-73
b=-73/3
b=-24+1/3

See similar equations:

| -x/9=-50 | | -2y+11=6y+35 | | h-2/3=6 | | -17p=-16p+20 | | 22=d/2+17 | | -9−1p=9−7p | | 25=-7w+3(w+3) | | 12u-6=-30 | | b-6/7=4/7 | | 5(m-69)=75 | | 14p=-56 | | –9−1p=9−7p | | w/2-11=15 | | -17n+14n=3 | |      7x+10=-4 | | 3k+2-6=8k+3 | | 9p-40=3p | | 10-6v=-8-8v+4 | | 91=7(t-77) | | g-8.7=1.3 | | (z+8)2=22 | | q/10+84=93 | | 10x+86=180 | | 4.1n-18.98=-3.8n-11.87 | | -8p-4=-2p+3-7p | | -3(x=5)-2x=25 | | 3x/2+2x/3=39 | | -11w+12=-9w | | -33=-7z-5 | | 2x3-50x=0 | | 3p-40=3p- | | 10x+-4+90=180 |

Equations solver categories